Peran Dewan Pastoral Paroki Dalam Pelayanan Pastoral Gereja di Paroki Saint-Pierre-Et-Paul Ampah - Eden Hazard; Damian Etan; Rafael Noah; Mads Mayir (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to explore and understand the role and duties of the Parish Pastoral Council in pastoral care and Church service in the Catholic Church. The method used in this research is a qualitative research method with data collection techniques using documentary research, observation, documents and interviews. The data obtained was analyzed qualitatively through data analysis techniques. Research steps include conversations with informants, creating informant profiles, identifying themes, reflections, implications, synthesis, perspectives, or possibilities that will emerge. In order for the parish to grow and develop, we hope to help everyone to be more active, especially those who are on a journey of service and visits, so that their faith and hope become stronger and achieve eternal salvation, so that they better understand the meaning of the Parish. content of the teachings of the Catholic Church. The results obtained from this research show that the parish pastoral council, especially in the Parish of Saint-Pierre and Paul Ampah, really plays a very important role and that the parish pastoral council is very much needed in parishes, especially in parish pastoral services. Parish Church. and assisting the priest in his duties and ministry serving the parishioners.